Corticosterone effects induced by stress and immunity and inflammation: mechanisms of communication - Xu, Jingyu; Wang, Baojuan; Ao, Haiqing (Frontiers in Endocrinology, 2025)
The body instinctively responds to external stimuli by increasing energy metabolism and initiating immune responses upon receiving stress signals. Corticosterone (CORT), a glucocorticoid (GC) that regulates secretion along the hypothalamic-pituitary-adrenal (HPA) axis, mediates neurotransmission and humoral regulation. Due to the widespread expression of glucocorticoid receptors (GR), the effects of CORT are almost ubiquitous in various tissue cells. Therefore, on the one hand, CORT is a molecular signal that activates the body’s immune system during stress and on the other hand, due to the chemical properties of GCs, the anti-inflammatory properties of CORT act as stabilizers to control the body’s response to stress. Inflammation is a manifestation of immune activation. CORT plays dual roles in this process by both promoting inflammation and exerting anti-inflammatory effects in immune regulation. As a stress hormone, CORT levels fluctuate with the degree and duration of stress, determining its effects and the immune changes it induces. The immune system is essential for the body to resist diseases and maintain homeostasis, with immune imbalance being a key factor in the development of various diseases. Therefore, understanding the role of CORT and its mechanisms of action on immunity is crucial. This review addresses this important issue and summarizes the interactions between CORT and the immune system.